Successful Therapy of Refractory Erythema Nodosum Associated with Crohn's Disease Using Potassium Iodide - John K Marshall; E Jan Irvine (Canadian Journal of Gastroenterology)
Erythema nodosum is a common extraintestinal manifestation of Crohn's disease. While mild skin involvement often responds to conservative management, severe or refractory cases may require systemic corticosteroid or immunosuppressive therapy. This report describes successful treatment of severe, refractory erythema nodosum associated with Crohn's colitis using oral potassium iodide. While the mechanism of action of this agent is poorly understood, it appears to be an effective and nontoxic therapy for Crohn's-related erythema nodosum and warrants further evaluation in a placebo controlled trial.